PENGARUH PROGRAM KARMA TERHADAP KEPERCAYAAN MASYARAKAT TENTANG DUNIA MISTIS DI DESA PASIR RINGGIT INDRAGIRI HULU - Ulfha Tri Hardianti; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The Karma program is one of the reality show programs presented by ANTV which reveals good karma dan bad karma based on participant birth. First appeared on 24 December 2017, to raised mysticism or public trust. Karma’s show is thought to have influenced the audience, especially for some people in Pasir Ringgit village who absorb whatever information they got watching television. According to cultivation theory, the television is a medium for learning about society and culture in the environment. This perception is awakened from the mind about society and culture is largely determined by television. Cultivation theory focuses more on how people perceive social reality after he watches television. In other words, the media influences the audience and each the audience believe it. By looking at the phenomena, the researchers want to see how the Karma ANTV program influences the public’s trust in Pasir Ringgit Village.The method used is explanative quantitative using purposive sampling technique and the number of samples as mus as 96 respondents. Researchers collected data with questionnaires. To find out there is any influence between variable X and variable T, researches use simple lier regression analysis. To process the test questionnaires data is done by using SPSS program Windows version 16.Based on the results of simple linear regression gets the value of regression coefficient in this research is Y= 9,043 + 0,239 X with a significance level of 0,000. Of course it’s smalle than α= 0,05. Its means that there is influence of the Karma’s program on public trust in trust in the mystical world in the Pasir Ringgit Village Indragiri Hulu by 33,3% and classified as low of influence. Although not dominant but respondents pay attention to the contents of the message conveyed and tick the public trust arise.